Design and Development of Pedal Pump for Low-Lift Irrigation - Islam, M Serazul; Hossain, M Zakaria; Khair, M Abul (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A study was undertaken to design and construct a low-lift pedal pump for use in small irrigation project areas. For this purpose, different types of piston valves and check valves were constructed and tested at different suction heads in the laboratory to evaluate their performances. After several trials, Piston valve type-II and check valve type-III were found to be suitable. The average discharges of the pumps ranged from 93.27 to 53.27 litre per second were noted against heads of 0.60 to 2.0 m respectively, when piston valve type-II and check valve type-III were used. During pedal pump operation, less input power was needed and it can be operated by one adult man for a long time (more than 2 hours) continuously without being tired. Efficiency of the pump was 46.53 percent against a head of 1.65 m. The pedal pump can be constructed using local materials and skill. It would be suitable to irrigate small and fragmented land holdings, especially to pump water from a shallow depth (up to 2 m) to irrigate small plots like vegetables and seed beds with less physical effort. Key words: Pedal pump, discharge rate, power requirement, efficiency, piston valve and check valve. Â DOI = 10.3329/jard.v5i1.1468 J Agric Rural Dev 5(1&2), 116-126, June 2007